Penentuan Penerima Bantuan dengan Program Miskin Berprestasi Menggunakan Metode Combined Compromise Solution (CoCoSo) - Sallaby, Achmad Fikri; Kanedi, Indra; Sari, Venny Novita; Alinse, Rizka Tri; Supardi, Reno (Journal of Computer System and Informatics (JoSYC), 2024)
Educational assistance programmes from the government and other parties allow people to focus on education without being burdened by costs. In Indonesia, various aid programmes are available, including Bidik Misi for new students and special programmes for active students in need. These programmes aim to help poor, high-achieving students continue their education. However, there are problems in the determination of aid recipients. Aid funds are often misused by some students for hedonistic lifestyles. This is due to a selection system that is not objective and is still influenced by "insider power". Assessments based on students' economic conditions and achievements are often ignored, and priority is given to students who have connections in related institutions. This practice contradicts the purpose of the educational assistance programme, which is supposed to help students with economic limitations. Therefore, this research uses a Decision Support System (SDM). This study involved 15 students as data samples and used 5 assessment criteria. The selection of data samples was carried out by applying the Combined Compromise Solution method, one of the methods in decision making. From the selection process, 3 students were selected who were entitled to receive assistance. They are Siti Humairoh with a final score of 2.5395, Hafid Bangko in second place with a score of 2.2353, and Syfa Zahra in third place with a score of 2.1629. The three students have fulfilled all the requirements and they can proceed to the initial data validation process.